Effects of Transcutaneous Electrical Nerve Stimulation along With Home Based Care Program on Low Back Pain and Disability in Post-Partum Patients - Shafiq, Hira; Tauqeer, Sana; Hanif, Arooj; Zahid, Ambreen; Asghar, Momna; Nawaz, Umbar (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the Effects of Transcutaneous Electrical Nerve Stimulation Along with home based care program in postpartum patient with low back pain for improving pain and disability Study design: Quasi-Experimental study Place and duration: Kanaan Physiotherapy and spine Clinic Lahore, Pakistan from 2 March 2021-3 September 2021. Methodology: A total of 70 postpartum patients age range between 18years-40years were randomly allocated in 2 groups. Inclusion criteria was patients having low back pain during delivery and any other syndrome or anatomical abnormality were excluded. Group A received TENS plus supervised conventional home physical therapy program while Group B received Conventional home physical therapy program. Both groups took 5 sessions in a week treatment. Generalized the low back pain was measured by numeric pain scale, Modified Oswestry disability questionnaire was used to assess disability. Data analysis was done by using SPSS Version 21. Results: The experimental group showed significant improvement low back pain postpartum in numeric rating pain scale (p<0.00) (Pain) and Oswestry disability index (p<0.00) (Disability) Conclusion: It was concluded that Transcutaneous Electrical Nerve Stimulation along with home based exercise was significantly in reducing low back pain in postpartum. Comparison between both groups showed significant improvement in decreasing disability and pain after treatment.